Pengaruh Tingkat Konsentrasi Pupuk Daun Terhadap Pertumbuhan dan Hasil Cabai Merah Keriting (Capsicum annuum L.) Varietas Laju F1 - Dewi Firnia; Sarah Ayuni; Imas Rahmawati; Putra Utama; Andi Apriany Fatmawaty (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2023)
This study aims to determine the effect of various concentrations of leaf fertilizer on red chili (Capsicum annum L.) of the Laju F1 variety cultivation. This research was conducted at the experimental garden Instalasi Penelitian dan Pengkajian Teknologi Pertanian Balai Penelitian Tanaman Sayuran Serpong (IP2TP Balitsa Serpong). The method used in this research was the experimental method of Randomized Block Design with one factor, namely giving various levels of concentration leaf fertilizer consisting of six treatment levels namely 0; 1; 2; 3; 4; and 5 g/l with a total of 5 replication to obtain 30 experimental units. The results showed that leaf fertilizer has a significant effect on the average plant height parameter at 5 weeks after planting (WAP) (53.12 cm); stem diameter 3 WAP (3,99 mm), 4 WAP (6.85 mm), and 5 WAP (8.87 mm); fruit length per plant at 2nd harvest (15.55 cm); and fruit diameter per plant at 1st harvest (9.26 mm) and at 2nd harvest (9.77 mm); fruit weight per plant (1157,54 g); and fruit weight per plot (2673,34 g). The treatment of various concentrations of leaf fertilizers showed no significant differences in the parameters of the amount of fruit per plant.